Expediting venous drainage in large anterolateral thigh flaps for scalp electrical burns in India: two case reports on the use of primary vein grafts for second vein anastomosis - Jyotica Jagadish Chawaria; Parvati Ravula; Nazia Tabassum; Srikanth Rangachari (Journal of Trauma and Injury)
Large scalp defects resulting from high-voltage electrical burns require free flaps, preferably skin, to permit optimal coverage and enable future or simultaneous cranial vault reconstruction. The anterolateral thigh permits the harvest of a large area of skin supplied by a reliable perforator. The superficial temporal vessels offer the proximate choice of recipient vessels to enable adequate reach and coverage. The lack of a second vein at this site implies the inability to perform a second venous anastomosis; however, this obstacle can be overcome by using an interposition vein graft, to the neck veins primarily. This assures adequate venous drainage and complete flap survival.